A release film for ultra-thin lithium strip calendering and its preparation method and application
By adding ultra-high molecular weight polyethylene to the release film to form a crosslinking network, the existing release film has solved the problem of taking into account both friction and release force, and the smooth molding and wear resistance of lithium foil during high-speed calendering are achieved.
Patent Information
- Application Number
- CN202410691161.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing release films are difficult to achieve a good balance in terms of friction and release force, especially in products that require ultra-light release force and large static friction coefficient, there is a risk of uneven group distribution, and the wear resistance of polyethylene wax particles is insufficient, making it difficult to improve scratch resistance.
A release film for ultra-thin lithium belt calendering is adopted. By adding ultra-high molecular weight polyethylene to the silicone system, a cross-linking network is formed to improve wear resistance and toughness, and at the same time, a nano-scale concave and convex structure is formed during the cooling process to increase friction.
The problem of the lithium foil being able to be smoothly formed without slipping or deformation during high-speed calendering process, it has excellent wear resistance and self-lubricity, and can produce thinner lithium tape or lithium foil at higher calendering speeds.
Smart Images

Figure CN118530660B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of release film preparation, and in particular to a release film for ultra-thin lithium strip rolling, and a preparation method and application thereof. Background Art
[0002] During the first charge and discharge process of lithium-ion batteries, a large amount of electrolyte and lithium ions released from the positive electrode material will be consumed, resulting in irreversible capacity loss, resulting in lower coulombic efficiency, reduced battery energy density and cycle life; in order to solve this problem, pre-lithiation technology provides an effective solution. This technology can significantly improve the initial coulombic efficiency of the negative electrode, reduce the consumption of lithium during the irreversible charging process of the positive electrode, and improve the battery energy density; among them, the rolled lithium foil composite negative electrode is an effective pre-lithiation method and is currently an important way to achieve the industrial production of pre-lithium batteries.
[0003] Lithium foil is generally formed by calendering. Lithium-platinum products have high requirements for surface smoothness, thickness uniformity and thickness. The preparation of wide and thin lithium foil is the main problem currently faced. On the one hand, it puts forward high requirements for the process, and on the other hand, it also has high requirements for the performance of the release film. In particular, in order to use a wider calendering rate, the release film is required to ensure that the greater friction force can be smoothly formed without slipping of lithium metal, and secondly, it must ensure that it has a very light release force so that the lithium foil and the release film can be smoothly separated during the rapid production process. However, it is difficult for the existing release film to achieve a good balance between friction and release force.
[0004] For example, Chinese patent CN 117126406A regulates friction and release force through polar molecules, but can only achieve balance within a certain range. This is difficult to meet for products that require ultra-light release force with a large static friction coefficient, and there is a risk of uneven group distribution.
[0005] For example, Chinese patent CN 107627700A uses polyethylene wax particles, but polyethylene wax particles do not have excellent wear resistance and are difficult to improve the anti-scratch performance of the release film. Secondly, polyethylene wax is miscible with the solvent in the release agent formula system and cannot maintain its granular shape, which cannot overcome the above-mentioned technical problems. Summary of the invention
[0006] The purpose of the present invention is to solve at least one of the technical problems existing in the above-mentioned prior art, and to provide a release film for ultra-thin lithium strip rolling and a preparation method and application thereof.
[0007] The technical solution of the present invention is as follows:
[0008] A release film for ultra-thin lithium strip calendering, comprising the following raw materials in parts by weight:
[0009] 100 parts of vinyl polysiloxane, 5-20 parts of hydrogen-containing polysiloxane, 5-20 parts of ultra-high molecular weight polyethylene, 1-5 parts of release force regulator, 5-10 parts of anchoring agent, 0.05-0.5 parts of peroxide catalyst, 1-5 parts of platinum catalyst, and 100-500 parts of solvent.
[0010] Preferably, it includes at least one of the following technical features:
[0011] The release force regulator is a hydrocarbon-modified MDQ silicone resin;
[0012] The anchoring agent is epoxypropyltriethoxysilane;
[0013] The peroxide catalyst is dicumyl peroxide;
[0014] The platinum catalyst is chloroplatinic acid;
[0015] The solvent is 120# solvent oil.
[0016] Preferably, it includes at least one of the following technical features:
[0017] The molecular weight of the ultra-high molecular weight polyethylene is 1 million to 4 million;
[0018] The viscosity of the vinyl polysiloxane is 100-5000cp, and the content of vinyl is 10-30mmol / g;
[0019] The viscosity of the hydrogen-containing polysiloxane is 10-200 cp, and the hydrogen content is 100-500 mmol / g.
[0020] The present invention also discloses a method for preparing a release film for ultra-thin lithium strip calendering, comprising the following steps:
[0021] S1: dissolving ultra-high molecular weight polyethylene in a solvent to obtain an ultra-high molecular weight polyethylene solution;
[0022] S2: adding vinyl polysiloxane, hydrogen-containing polysiloxane, release force regulator, anchoring agent, peroxide catalyst and platinum catalyst into the ultra-high molecular weight polyethylene solution and mixing to obtain a mixed solution;
[0023] S3: coating the mixed solution on a substrate, drying and curing the mixture to obtain a release film.
[0024] Preferably, in step S3, the drying and curing temperature is 120-200° C. and the time is 0.5-3 min.
[0025] Preferably, the substrate is a PET substrate with a thickness of 20 to 50 μm.
[0026] Preferably, the coating thickness of the release film is 1 to 5 μm.
[0027] Preferably, the release force of the release film is 1 to 5 g / in, and the static friction coefficient is 0.04 to 0.08.
[0028] The invention also discloses an application of the release film in preparing an ultra-thin lithium strip.
[0029] Preferably, at a rolling speed of 5 to 10 m / min, a lithium strip of 10 to 30 μm is produced.
[0030] The beneficial effects of the present invention are:
[0031] (1) The release film for ultra-thin lithium strip calendering of the present invention adds ultra-high molecular weight polyethylene with excellent wear resistance and self-lubricating properties to a silicone system release agent, which can effectively improve the wear resistance of the composite system without increasing the release force.
[0032] (2) The release film for ultra-thin lithium strip calendering of the present invention has ultra-high molecular weight polyethylene and silicone added to form a cross-linked network, which further increases the strength and toughness of the release film and ensures that it will not deform, slip, or have other problems during high-speed calendering.
[0033] (3) In the release film for calendering an ultra-thin lithium strip of the present invention, the added ultra-high molecular weight polyethylene is evenly dispersed in the release agent layer, and the distributed polyethylene molecular chains are anchored by chemical cross-linking to prevent large-scale shrinkage from causing excessive local deformation of the release film. During the cooling process, the arrangement of local ultra-high molecular weight molecular segments will form micro-region crystallization, and the inconsistent shrinkage of the two phases will result in the presence of nano-scale concave-convex structures on the film surface, which can improve the friction force during the calendering process and ensure that the lithium foil can move smoothly with the release film during high-speed calendering.
[0034] (4) The release film for ultra-thin lithium strip rolling of the present invention has a solvent release agent which can make the thickness of the release agent more uniform, and is more suitable for the preparation of wide and thin lithium foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the microstructure of the release film of the present invention. DETAILED DESCRIPTION
[0036] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0037] One embodiment of the present invention provides a release film for ultra-thin lithium strip rolling, comprising the following raw materials in parts by weight:
[0038] 100 parts of vinyl polysiloxane, 5-20 parts of hydrogen-containing polysiloxane, 5-20 parts of ultra-high molecular weight polyethylene, 1-5 parts of release force regulator, 5-10 parts of anchoring agent, 0.05-0.5 parts of peroxide catalyst, 1-5 parts of platinum catalyst, and 100-500 parts of solvent.
[0039] The present invention adds ultra-high molecular weight polyethylene to the organosilicon system. On the one hand, the wear resistance of the composite system can be improved while ensuring that the release force does not change much, because the ultra-high molecular weight polyethylene itself has excellent wear resistance and self-lubricating properties; at the same time, the ultra-high molecular weight polyethylene and the organosilicon form a cross-linked network, see Figure 1 , further enhancing the toughness of the release film; on the other hand, the ultra-high molecular weight polyethylene is evenly dispersed in the release film layer, and micro-region crystallization will form during the cooling process. The inconsistent contraction of the two phases will result in the existence of nano-scale concave-convex structure on the surface of the film, which can improve the friction during the calendering process and ensure that the lithium foil can move forward smoothly with the release film during high-speed calendering.
[0040] In some embodiments, the release force regulator is a hydrocarbon-modified MDQ-type silicone resin;
[0041] The anchoring agent is epoxypropyltriethoxysilane;
[0042] The peroxide catalyst is dicumyl peroxide;
[0043] The platinum catalyst is chloroplatinic acid;
[0044] The solvent is 120# solvent oil.
[0045] In some embodiments, the molecular weight of the ultra-high molecular weight polyethylene is 1 million to 4 million. Specifically, the molecular weight of the ultra-high molecular weight polyethylene can be 1 million, 1.2 million, 1.3 million, 1.8 million, 2 million, 2.5 million, 2.8 million, 3 million, 3.5 million or 4 million.
[0046] The viscosity of the vinyl polysiloxane is 100-5000cp, and the content of vinyl is 10-30mmo l / g. Specifically, the viscosity of the vinyl polysiloxane can be 100cp, 500cp, 1000cp, 1500cp, 2000cp, 2500cp, 3000cp, 3500cp, 4000cp, 4500cp or 5000cp, and the viscosity is the viscosity at room temperature; the content of vinyl can be 10mmo l / g, 12mmo l / g, 15mmo l / g, 20mmo l / g, 25mmo l / g or 30mmo l / g.
[0047] The viscosity of the hydrogen-containing polysiloxane is 10 to 200 cp, and the hydrogen content is 100 to 500 mmol / g; specifically, the viscosity of the hydrogen-containing polysiloxane may be 10 cp, 20 cp, 30 cp, 40 cp, 50 cp, 60 cp, 100 cp, 120 cp, 150 cp or 200 cp, and the viscosity is the viscosity at room temperature; the hydrogen content is 100 mmol / g, 150 mmol / g, 200 mmol / g, 250 mmol / g, 300 mmol / g, 350 mmol / g, 400 mmol / g, 450 mmol / g or 500 mmol / g.
[0048] It should be noted that the above-mentioned viscosity at room temperature refers to the viscosity at 25-35°C.
[0049] Another embodiment of the present invention provides a method for preparing a release film for ultra-thin lithium strip rolling, comprising the following steps:
[0050] S1: dissolving ultra-high molecular weight polyethylene in a solvent to obtain an ultra-high molecular weight polyethylene solution;
[0051] S2: adding vinyl polysiloxane, hydrogen-containing polysiloxane, release force regulator, anchoring agent, peroxide catalyst, and platinum catalyst into the ultra-high molecular weight polyethylene solution and mixing to obtain a mixed solution;
[0052] S3: coating the mixed solution on a substrate, drying and curing the mixture to obtain a release film.
[0053] In some embodiments, in step S3, the drying and curing temperature is 120-200° C., and the time is 0.5-3 min.
[0054] The preparation method of the present invention obtains good wear resistance and a cross-linked network microstructure by adding an ultra-high molecular weight polyethylene solution to an organic silicon system, thereby improving the toughness of a release film. Meanwhile, the ultra-high molecular weight polyethylene is evenly dispersed in a release agent layer, and the distributed polyethylene molecular chains are anchored by chemical cross-linking to prevent large-scale shrinkage from causing excessive local deformation of the release film. During the cooling process, the arrangement of local ultra-high molecular weight molecular segments forms micro-region crystallization, and the inconsistent shrinkage of different phases results in a nano-scale concave-convex structure on the film surface, thereby ensuring that deformation, slippage and other problems will not occur during high-speed calendering.
[0055] In some embodiments, the substrate is a PET substrate having a thickness of 20 to 50 μm. Specifically, the thickness of the substrate may be 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.
[0056] In some embodiments, the coating thickness of the release film is 1-5 μm. Specifically, the coating thickness of the release film may be 2 μm, 3 μm, 4 μm or 5 μm.
[0057] In some embodiments, the release film has a release force of 1-5 g / in and a static friction coefficient of 0.04-0.08.
[0058] Another embodiment of the present invention provides an application of the above-mentioned release film in the preparation of ultra-thin lithium strips, and its specific implementation method is to place a lithium strip (generally greater than 100 μm) between an upper release film and a lower release film, and then adjust the gap, pressure, speed and other parameters of the two rollers to roll the lithium strip into an ultra-thin lithium foil, and finally peel off the upper and lower release films to achieve the winding of the ultra-thin lithium foil.
[0059] In some embodiments, at a calendering speed of 5-10 m / min, a lithium tape of 10-30 μm is produced; specifically, at a calendering speed of 7.5 m / min, a lithium tape of 13 μm is produced; at a calendering speed of 6.5 m / min, a lithium tape of 22 μm is produced; at a calendering speed of 9.0 m / min, a lithium tape of 16 μm is produced.
[0060] The present invention adds ultra-high molecular weight polyethylene to the organosilicon system. Since the ultra-high molecular weight polyethylene has good wear resistance and good crystallization effect, it can give the release layer good wear resistance, low friction and a suitable static friction coefficient after cross-linking, so that thinner lithium strips or lithium foils can be produced at a higher calendering speed, solving the problems of deformation, wrinkling and cracking of the release film in the high-speed calendering process in the traditional method.
[0061] The technical solution of the present invention is further described below through specific embodiments.
[0062] Example 1
[0063] 1) Select 10 parts of ultra-high molecular weight polyethylene with a molecular weight of 2.5 million and 200 parts of 120# solvent oil, stir and completely dissolve them at 150°C to obtain an ultra-high molecular weight polyethylene solution;
[0064] 2) adding 100 parts of vinyl polysiloxane (500 cps, vinyl content 25 mmol / g), 10 parts of hydrogen-containing polysiloxane (100 cps, hydrogen content 300 mmol / g), 2 parts of release force regulator (hydrocarbon-modified MDQ silicone resin), 6 parts of anchoring agent (epoxypropyltriethoxysilane), 0.1 parts of peroxide catalyst (diisopropyl peroxide), and 2 parts of platinum catalyst (chloroplatinic acid-isopropyl alcohol) to the ultra-high molecular weight polyethylene solution and stirring uniformly to obtain a mixed solution;
[0065] 3) coating the mixed solution on a 30 μm PET substrate by blade coating;
[0066] 4) After the coating is completed and the solvent evaporates, it is dried and cured in a continuous oven;
[0067] 5) By adjusting the coating rate, a release film with a release coating thickness of 2.5 μm was obtained.
[0068] Example 2
[0069] 1) Select 10 parts of ultra-high molecular weight polyethylene with a molecular weight of 1.5 million and 200 parts of 120# solvent oil, stir and completely dissolve them at 150°C to obtain an ultra-high molecular weight polyethylene solution;
[0070] 2) adding 100 parts of vinyl polysiloxane (500 cps, vinyl content 25 mmol / g), 10 parts of hydrogen-containing polysiloxane (100 cps, hydrogen content 300 mmol / g), 2 parts of release force regulator (hydrocarbon-modified MDQ silicone resin), 6 parts of anchoring agent (epoxypropyltriethoxysilane), 0.1 parts of peroxide catalyst (diisopropyl peroxide), and 2 parts of platinum catalyst (chloroplatinic acid-isopropyl alcohol) to the ultra-high molecular weight polyethylene solution and stirring uniformly to obtain a mixed solution;
[0071] 3) coating the mixed solution on a 30 μm PET substrate by blade coating;
[0072] 4) After the coating is completed and the solvent evaporates, it is dried and cured in a continuous oven;
[0073] 5) By adjusting the coating rate, a release film with a release coating thickness of 2.5 μm was obtained.
[0074] Example 3
[0075] 1) Select 15 parts of ultra-high molecular weight polyethylene with a molecular weight of 2.5 million and 300 parts of 120# solvent oil, stir and completely dissolve them at 150°C to obtain an ultra-high molecular weight polyethylene solution;
[0076] 2) adding 100 parts of vinyl polysiloxane (500 cps, vinyl content 25 mmol / g), 10 parts of hydrogen-containing polysiloxane (100 cps, hydrogen content 300 mmol / g), 2 parts of release force regulator (hydrocarbon-modified MDQ silicone resin), 6 parts of anchoring agent (epoxypropyltriethoxysilane), 0.1 parts of peroxide catalyst (diisopropyl peroxide), and 2 parts of platinum catalyst (chloroplatinic acid-isopropyl alcohol) to the ultra-high molecular weight polyethylene solution and stirring uniformly to obtain a mixed solution;
[0077] 3) coating the mixed solution on a 30 μm PET substrate by blade coating;
[0078] 4) After coating, the solvent is evaporated and then dried and cured in a continuous oven;
[0079] 5) By adjusting the coating rate, a release film with a release coating thickness of 2.5 μm was obtained.
[0080] Comparative Example 1 (without adding ultra-high molecular weight polyethylene solution)
[0081] 1) 100 parts of vinyl polysiloxane (500 cps, vinyl content 25 mmol / g), 10 parts of hydrogen-containing polysiloxane (100 cps, hydrogen content 300 mmol / g), 2 parts of release force regulator (hydrocarbon-modified MDQ silicone resin), 6 parts of anchoring agent (epoxypropyltriethoxysilane), and 2 parts of platinum catalyst (chloroplatinic acid-isopropyl alcohol) were mixed uniformly to obtain a mixed solution;
[0082] 2) coating the mixed solution on a 30 μm PET substrate by blade coating;
[0083] 3) After the coating is completed and the solvent evaporates, it is dried and cured in a continuous oven;
[0084] 4) By adjusting the coating rate, a release film with a release coating thickness of 2.5 μm was obtained.
[0085] Comparative Example 2 (no peroxide catalyst added, i.e. no cross-linking reaction)
[0086] 1) Select 10 parts of ultra-high molecular weight polyethylene with a molecular weight of 2.5 million and 200 parts of 120# solvent oil, stir and completely dissolve them at 150°C to obtain an ultra-high molecular weight polyethylene solution;
[0087] 2) adding 100 parts of vinyl polysiloxane (500 cps, vinyl content 25 mmol / g), 10 parts of hydrogen-containing polysiloxane (100 cps, hydrogen content 300 mmol / g), 2 parts of release force regulator (hydrocarbon-modified MDQ silicone resin), 6 parts of anchoring agent (epoxypropyltriethoxysilane), and 2 parts of platinum catalyst (chloroplatinic acid-isopropanol) to the ultra-high molecular weight polyethylene solution and stirring to obtain a mixed solution;
[0088] 3) coating the mixed solution on a 30 μm PET substrate by blade coating;
[0089] 4) After the coating is completed and the solvent evaporates, it is dried and cured in a continuous oven;
[0090] 5) preparing a release film with a release coating thickness of 2.5 μm by adjusting the coating rate;
[0091] Comparative Example 3 (using low-density polyethylene)
[0092] 1) Select 10 parts of low-density polyethylene with a molecular weight of 200,000 and 200 parts of 120# solvent oil, stir and completely dissolve them at 150°C to obtain a low-density polyethylene solution;
[0093] 2) adding 100 parts of vinyl polysiloxane (500 cps, vinyl content 25 mmol / g), 10 parts of hydrogen polysiloxane (100 cps, hydrogen content 300 mmol / g), 2 parts of release force regulator (hydrocarbon-modified MDQ silicone resin), 6 parts of anchoring agent (epoxypropyltriethoxysilane), 0.1 parts of peroxide catalyst (diisopropyl peroxide), and 2 parts of platinum catalyst (chloroplatinic acid-isopropyl alcohol) to the low-density polyethylene solution and stirring uniformly to obtain a mixed solution;
[0094] 3) coating the mixed solution on a 30 μm PET substrate by blade coating;
[0095] 4) After the coating is completed and the solvent evaporates, it is dried and cured in a continuous oven;
[0096] 5) preparing a release film with a release coating thickness of 2.5 μm by adjusting the coating rate;
[0097] The release films prepared in the above embodiments and comparative examples were subjected to the following performance tests, and the test results are shown in Table 1.
[0098] The release force and static friction coefficient of the release film were tested at different positions. The release force test reference standard FTM10; the static friction coefficient test reference standard GB / T 10006-2021.
[0099] Preparation of lithium foil: Ultra-thin lithium foil is prepared by calendering with the prepared release film. The thickness of the lithium strip before calendering is about 200μm. During the calendering process, the release film is attached to the upper and lower parts for auxiliary calendering. After calendering, the release film is torn off to obtain ultra-thin lithium foil. During the calendering process, the thickness is adjusted by adjusting the roller gap, roller speed, roller pressure, etc. After calendering, the use effect of the release film is comprehensively evaluated by the peeling effect of the lithium foil and the release film, the integrity of the lithium foil, etc. First, the thickness is optimized, and the production rate is optimized while ensuring the minimum thickness that can be achieved. Finally, the optimized lithium foil thickness and calendering speed are obtained.
[0100] Table 1 Performance test results of embodiments and comparative examples
[0101] sample Release force (g / in) Static friction coefficient Optimized lithium foil thickness and rolling speed Example 1 2.8±0.113 0.056±0.0017 13μm, 7.5m / min Example 2 3.6±0.096 0.041±0.0012 22μm, 6.5m / min Example 3 3.1±0.135 0.062±0.0021 16μm, 9.0m / min Comparative Example 1 2.3±0.042 0.032±0.0008 17μm, 3.5.0m / min Comparative Example 2 4.5±0.165 0.065±0.0026 27μm, 8.5m / min Comparative Example 3 6.6±0.217 0.078±0.0032 35μm, 9.5m / min
[0102] The production of ultra-thin lithium foil requires that it be as fast as possible while being as thin as possible. The general target requirements are a thickness of less than 25 μm and a speed of more than 5 m / min. From the results in Table 1, it can be seen that the molecular weight of the ultra-high molecular weight polyethylene in Example 1 is higher than that in Example 2, the self-lubricating effect is better, and the friction coefficient is also larger, so a thinner thickness and faster speed calendering effect (13 μm and 7.5 m / min) can be achieved; in Example 3, the ultra-high molecular weight polyethylene content is increased, so that the release force and the static friction coefficient are increased, and a calendering effect of 16 μm thickness and 9 m / min speed can be achieved. From the comparative examples, comparative example 1 shows that although the release film without the addition of ultra-high molecular weight polyethylene can achieve a lower release force, its friction force is relatively low and it is difficult to meet the requirements of rapid production; comparative example 2 shows that the release force of the sample without cross-linking is increased, and the static friction coefficient is increased. Although the speed can be fast, the lithium foil thickness can be 27μm, and it is difficult to produce thinner lithium foil below 25μm; comparative example 3 uses low molecular weight polyethylene, has no lubricating effect, and the release force is significantly increased. Although the speed can reach 9.5m / min, the thickness of the lithium foil achieved is as high as 30μm or more, and it is still difficult to produce thinner lithium foil. The above results show that it is difficult to prepare lithium foil that meets the above-mentioned target requirements without the addition of ultra-high molecular weight polyethylene (comparative example 1), or without cross-linking (comparative example 2), or with the use of low molecular weight polyethylene (comparative example 3). However, the examples of the present application can achieve the target lithium foil. The main reasons are as follows: See Figure 1 The ultra-high molecular weight polyethylene (1-4 million) and silicone in the polysiloxane used in the embodiment can form a double cross-linked network microstructure through a unique catalytic cross-linking reaction, which can give the release layer good wear resistance, low release force and suitable static friction coefficient. The release layer is strong and tough and can withstand the greater pressure and shear force during the calendering process of the ultra-thin lithium strip, and is better used in the preparation of wide and thin lithium foil under high-speed calendering.
[0103] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all these changes and deformations should fall within the scope of protection of the claims of the present invention.
Claims
1. A release film for ultra-thin lithium strip rolling, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of vinyl polysiloxane, 5-20 parts of hydrogen-containing polysiloxane, 5-20 parts of ultra-high molecular weight polyethylene, 1-5 parts of release force regulator, 5-10 parts of anchoring agent, 0.05-0.5 parts of peroxide catalyst, 1-5 parts of platinum catalyst, and 100-500 parts of solvent; The molecular weight of the ultra-high molecular weight polyethylene is 1 million to 4 million.
2. The release film for ultra-thin lithium strip rolling according to claim 1, characterized in that: At least one of the following technical features: The release force regulator is a hydrocarbon-modified MDQ silicone resin; The anchoring agent is epoxypropyltriethoxysilane; The peroxide catalyst is dicumyl peroxide; The platinum catalyst is chloroplatinic acid; The solvent is 120# solvent oil.
3. The release film for ultra-thin lithium strip rolling according to claim 1, characterized in that: At least one of the following technical features: The viscosity of the vinyl polysiloxane is 100 to 5000 cp, and the content of vinyl is 10 to 30 mmol / g; The hydrogen-containing polysiloxane has a viscosity of 10 to 200 cp and a hydrogen content of 100 to 500 mmol / g.
4. A method for preparing a release film for ultra-thin lithium strip rolling as claimed in claim 1, characterized in that: The following steps are involved: S1: dissolving ultra-high molecular weight polyethylene in a solvent to obtain an ultra-high molecular weight polyethylene solution; S2: adding vinyl polysiloxane, hydrogen-containing polysiloxane, release force regulator, anchoring agent, peroxide catalyst and platinum catalyst into the ultra-high molecular weight polyethylene solution and mixing to obtain a mixed solution; S3: coating the mixed solution on a substrate, drying and curing the mixture to obtain a release film.
5. The method for preparing a release film for ultra-thin lithium strip rolling according to claim 4, characterized in that: In step S3, the drying and curing temperature is 120-200° C. and the time is 0.5-3 min.
6. The method for preparing a release film for ultra-thin lithium strip rolling according to claim 4, characterized in that: The substrate is a PET substrate with a thickness of 20 to 50 μm.
7. The method for preparing a release film for ultra-thin lithium strip rolling according to claim 4, characterized in that: The coating thickness of the release film is 1 to 5 μm.
8. The method for preparing a release film for ultra-thin lithium strip rolling according to claim 4, characterized in that: The release force of the release film is 1 to 5 g / in, and the static friction coefficient is 0.04 to 0.
08.
9. Use of the release film as claimed in any one of claims 1 to 3 or the release film prepared by the preparation method as claimed in any one of claims 4 to 8 in preparing an ultra-thin lithium strip.
10. The use according to claim 9, characterized in that: At a rolling speed of 5 to 10 m / min, a lithium strip of 10 to 30 μm was obtained.
Citation Information
Patent Citations
Release film for flexible circuit boards
CN107627700A
UV (ultraviolet) type block light stripping additive and release film for lithium strip calendering based on additive
CN117126406A
Preparation process for conveniently stripped matte release film
CN104549973A
Smooth and elastic organic silicon release agent
CN109385207A